Structural studies of metalloproteins by NMR - Bagby, S (1991)
This thesis describes the application of one and two dimensional proton NMR spectroscopy and associated computational methods to the study of structure in solution of two metalloproteins: the cytochrome subunit (cytPCMH) of Pseudomonas putida para-cresol methylhydroxylase (PCMH) and parsley plastocyanin. Initial work on cytPCMH focused on the haem prosthetic group. Haem meso proton resonances were assigned by combined analysis of NOE data and the PCMH crystal structure. Interproton distances derived from these assignments indicated that one of the axial ligands to the haem Fe, Met 50, has a different orientation in cytPCMH in solution relative to that in crystalline PCMH. Further evidence for this difference between the unbound and bound states of the cytochrome subunit was provided by differences in reduction potentials, and by differences in the pattern of haem methyl group resonances of the oxidised species. Precedents for different ligand orientations among c-type cytochromes have been discussed. Aromatic and methyl group spin system assignment in cytPCMH was carried out as the initial stage of sequential resonance assignment and structure determination. Aromatic side chain assignments, combined with analysis of NOE data, provided further evidence for a local conformational change in cytPCMH relative to PCMH. A potentially important residue in the conformational change was identified. Essentially complete sequential resonance assignments have been obtained for parsley plastocyanin, which has important differences in sequence from other higher plant plastocyanins, and is closely related to some algal plastocyanins. Assignments were initially used in location and characterisation of elements of regular secondary structure. Distance and dihedral angle restraints were then accumulated and used in the calculation of a high resolution three dimensional structure of parsley plastocyanin. This structure has been analysed in detail and compared to reported structures of other plastocyanins. Features of interest include a β-bulge, a cis-Pro bend and a carboxyl---carboxylate hydrogen bond which accounts for parsley plastocyanin's anomalously high pKa . Residue deletions cause elimination of a turn found in most higher plant plastocyanins. This turn is located in an acidic patch binding site, which may be further disrupted in parsley plastocyanin by non-conservative substitution of two charged residues. Calculations show that these sequence differences result in diminution of the negative electrostatic field of parsley plastocyanin relative to that of poplar plastocyanin.